Análise teórica e experimental de lajes cogumelo nervuradas em escala reduzida - Dutra, Clairson (2005)
The experimental analysis of structures of reinforced concrete supplies subsidies to the knowledge of the behavior of structural parts built with this material. Experimental analysis in reduced scale brings great advantages in relation to experimentation of real size models, since the amount of used materials is lesser and the physical conditions for laboratory test, that in the majority of the times is a limiting subject, can be bypassed. This type of technology has a sound basis and this can be used to take the necessary advantage. The study of the strength and displacements in the ribbing flat slabs are the subject of this research, since in the geometry and loading cases not prescribed by NBR 6118:2003, the recommended simplified method presents discrepancies with the results predicted for ribbing flat slabs of diverse forms. Three equal models of this type of ribbing flat slab, in reduced scale, had been confectioned and instrumented with sights to get comparative data that validate or not the application of the simplified method for the analysis of this structural model recommended by the Brazilian Standard. For sake of comparison, a numerical model that uses the Finite Element Method was used, simulating the characteristics of the tested ribbing flat slab, with the application of software s ASYS and CYPECAD.